Problem Multikultural Pendidikan Islam - Fitriansyah, Muhammad Nurul (Tsamratul Fikri | Jurnal Studi Islam, 2020)
Education is a tool in forming someone's character. An education system that only emphasizes the transfer of knowledge alone makes education no longer meaningful and has a positive effect on students. Education that does not touch the affective domain makes students less moral so that it will cause social conflict. Multicultural education is a concept of education as a solution to socio-cultural conflicts in plural societies. In the course of multicultural education began to enter the area of religious education by carrying out the mission of religious pluralism, relativism and secular humanism. In the Islamic view, the concept of multicultural education tries to deconstruct the concept of God, which should be instilled in students. Therefore, Islamic education should apply the concept that was born from the teachings of Islam itself, namely the concept of tasamuh. This research uses literature review method by searching various sources of literature that are relevant to the research subject.